Presence of Cytomegalovirus Infection Is Associated With an Unfavorable Outcome in Immunocompetent Infants With Pertussis - Jiang, Wujun; Chen, Sainan; Xu, Lina; Xu, Xueyun; Huang, Li; Wang, Yuqing; Hao, Chuangli (Frontiers in Cellular and Infection Microbiology, 2022)
Background: We aimed to examine cytomegalovirus (CMV) infection in immunocompetent infants with pertussis, based on polymerase chain reaction in plasma and broncho alveolar lavage (BAL), and to assess the clinical characteristics and outcomes for these patients. Methods: We performed a prospective observational cohort study of consecutive infants with pertussis in Children’s Hospital of Soochow University between Jan 2017 and Jan 2020. We report the burden of CMV PCR in plasma and BAL within this patient group, and evaluate associations between CMV infection and pertussis in these hospitalized infants. Results: During the study period, 1967 infants <1 years were evaluated for pertussis, 190 infants were diagnosed as pertussis. For the 190 pertussis patients, 38 (20.0%) patients had positive CMV PCR in plasma. CMV PCR in plasma had high sensitivity and specificity for CMV PCR in BAL (81.3% and 94.4%, respectively). Children with positive CMV PCR in plasma were 3.67 times more likely to present with severe disease (OR 3.67; CI 1.61-8.36). Comparisons of duration of hospital stay curves using the log-rank test statistic demonstrated that the relative risk of longer hospital stay of positive CMV PCR relative to negative CMV was 1.51 (95% CI: 1.09 to 2.27, P = 0.01). Conclusions: Our study reported a high prevalence of CMV reactivation in immunocompetent infants with pertussis. The presence of CMV in plasma may be associated with an unfavorable outcome in infants with pertussis.h